Pengaruh p-Hidroksibenzoat dan Paraquat terhadap Pertumbuhan Tanaman Kedelai pada Lahan Gambut Pangkoh kalimantan Tengah = The Effect of p-Hydroxybenzoic Acid and Paraquat on The Soybean Growth in Pangkoh Peat Soil Centr - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The objective of this research was to investigate the effect of p-hydroxybenzoic acid and paraquat on the growth of soybean which planted in fibric and sapricpeat soil. The research was done at Kuningan green house and General Soil Science Laboratory, Agricultural Faculty of Gadjah Mada University, Yogyakarta. The pot experiment was designed in Complete Randomized Design (CRD) with 3 factors. The first factor was peat material, consisted of fibric and sapric. The second factor was paraquat concentration, consisted of two levels: 0 ppm and 20 ppm. The third factor was dose of p-hidroxybenzoic acid, consisted of four levels: 0, 20, 40 and 60 ppm. The plant were harvested of 80 days. Data analyzed with analysis of variance, followed by a Duncan's Multiple Range Test. The result of the research showed that p-hydroxybenzoic acid did not influence the vegetative growth of the plant. There was no significant difference from parameters of height of the plant, shoot and root dry weight, but had a negative effect on the generative growth of the plant. The decreasing of peas content, in sapric acid was lower than in fibric. Paraquat had negative effect on the vegetative and generative growth of plant, which showed from the height of the plant, shoots dry weight, root dry weight, peas content and grain weight. The existence orp-hydroxybenzoic acid in peat and the used of paraquat decreased yield of soybean, but did not influence on the vegetative growth of plant.